Corrosion Behavior of Carbon Steel in Alkaline, Deaerated Solutions: Influence of Carbonate Ions. Issue 6 (20th March 2020) - Martinelli-Orlando, Federico; Shi, Wei; Angst, Ueli
Abstract : The corrosion behavior of carbon steel was investigated in deaerated, moderately alkaline conditions (pH 9.8) at room temperature. This study was mainly focused on the influences of carbonate and bicarbonate ions, exposure time, and scale formation on the corrosion rate. The corrosion rate was calculated from Linear Polarization Resistance (LPR) measurements, Electrochemical Impedance Spectroscopy (EIS), analyzing Potentiodynamic Polarization (PDP) curves, and based on time-resolved dissolved iron concentration measurements through Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Surface characterization of corrosion products was performed by means of Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray analysis (EDX). The results showed that the presence of carbonate and bicarbonate significantly modified the corrosion behavior of the steel electrodes and gave rise to corrosion rates of several hundreds of μ m y −1, over time decreasing to levels around 100–200 μ m y −1 . This decrease in corrosion rate was related to scale formation that introduced a certain degree of mass transport limitations. Nevertheless, the corrosion rates remain relatively high, which has implications for engineering. To explain these high corrosion rates, a mechanistic model was proposed, including two combined effects: a chemical and an electrochemical effect. The different methods to determine corrosion rates were found to yield comparable results.